C‐H Oxidation by a Diiron Complex with Facially Opposing Active Sites. Issue 5 (6th February 2018) - Lindsay, Stacey; Mader, Sophie L.; Kaila, Ville R. I.; Hess, Corinna R.
Abstract: C−H oxidation is catalyzed by a high‐spin ferrous dimer, [(L 1 )2 Fe2 (CH3 CN)2 ](PF6 )4 (1 ), that offers two identical functional sites, separated by > 7 Å. The complex provides a unique contrast to both mononuclear and binuclear non‐heme enzyme active sites as well as biomimetic complexes. The oxidative activity of1 was examined using a range of substrates (cyclohexene, 9, 10‐dihydroanthracene, xanthene, triphenylmethane, triphenylphosphine, and cyclohexane) and PhIO as an oxidant. The studies establish the O‐atom transfer and H‐atom abstraction ability of the diiron complex. We further probe the energetics of cyclohexene oxidation by1 and derive putative mechanisms for the pathways of allylic alcohol and epoxide formation using density functional theory (DFT) calculations. The DFT calculations indicate that the oxidation reactions proceed via a Fe IV =O species in the triplet state, and that both iron centers can act independently of each other. The combined results provide insight into hydrocarbon oxidation by non‐coupled binuclear systems. Abstract : The high‐spin diiron complex, [(L 1 )2 Fe2 (CH3 CN)2 ](PF6 )4, has two independent active sites that catalyze C−H bond oxidation by competing O‐atom transfer and H‐atom abstraction mechanisms.